Eosinophils are part of the granulocyte response in tuberculosis and promote host resistance in mice - Bohrer,AC; Castro,E; Hu,Z; Queiroz,ATL; Tocheny,CE; Assmann,M; Sakai,S; Nelson,C; Baker,PJ; Ma,H; Wang,L; Zilu,W; et al. (Journal of Experimental Medicine, 2021)
Host resistance to Mycobacterium tuberculosis (Mtb) infection requires the activities of multiple leukocyte subsets, yet the roles of the different innate effector cells during tuberculosis are incompletely understood. Here we uncover an unexpected association between eosinophils and Mtb infection. In humans, eosinophils are decreased in the blood but enriched in resected human tuberculosis lung lesions and autopsy granulomas. An influx of eosinophils is also evident in infected zebrafish, mice, and nonhuman primate granulomas, where they are functionally activated and degranulate. Importantly, using complementary genetic models of eosinophil deficiency, we demonstrate that in mice, eosinophils are required for optimal pulmonary bacterial control and host survival after Mtb infection. Collectively, our findings uncover an unexpected recruitment of eosinophils to the infected lung tissue and a protective role for these cells in the control of Mtb infection in mice.